ZOMA: An Innovative Deep Learning Model for Early Childhood Education - Isnaini Jihan Luthfiana; Naila Fikrina Afrih Lia; Mursid Mursid (Journal of Education Research, 2026)
The Play Zone (ZOMA) Learning Model is an early childhood education innovation designed to holistically develop all aspects of a child’s development. This study aims to describe the development, structure, and implementation of the Play Zone (ZOMA) Learning Model as a child-centered early childhood education innovation at the IT Permata Hati Kindergarten, Semarang. This study employs a descriptive qualitative approach. Data were collected through direct observation, in-depth interviews with the principal and classroom teachers, and learning documentation. The research subjects included the Principal, 2 teachers, and 13 students in Group A. The ZOMA model integrates three theoretical pillars—Piaget’s cognitive development, Vygotsky’s social constructivism, and Montessori’s independence—into 6 active development zones. The strength of this model lies in the density of its micro-elements, where each type of play activity must incorporate all 6 elements simultaneously (sensory-motor, role-play, construction, numeracy, literacy, and religion and character) by utilizing natural materials from the surrounding environment (loose parts). The ZOMA model effectively breaks down the physical limitations of school facilities and the constraints of teacher availability through the design of meaningful, flexible, and holistically integrated play.